The Use of STAD to Improve Bahasa Indonesia Achievement in Junior High School Students - Hapsari, Elisabet Widyaning; Murtini (ANIMA Indonesian Psychological Journal, 2012)
Indonesian language (Bahasa) lesson is one of the lessons which was tested each year in the national exams. The average of Indonesian’s grade is 65, which is below the kriteria kelengkapan minimal (KKM = minimal completeness criteria) value (70). Values obtained were also influenced by students' learning methods provided by the teacher. The purpose of this study is to test the effectiveness of STAD methods to improve the performance of Bahasa lesson for junior high school children. Participants of thisstudy were 72 students in junior high school, who were divided into an experimental group (36 students) who receive the STAD method, and 36 students as the control who receive the traditional learning. This study use an experimental pre- and posttest design with switching replications. Results (p< .05) reveal that STAD could increase Bahasa (Indonesian language) achievement in junior high school. Bahasa Indonesia adalah salah satu yang diujikan dalam ujian nasional. Rata-rata nilai yang diperoleh (65) berada di bawah nilai kriteria kelengkapan minimal KKM (70). Nilai yang diperoleh juga dipengaruhi metode belajar siswa yang diperoleh dari guru. Studi ini menguji kefektifan metode pembelajaran kooperatif STAD (Student Teams-Achievement Divisions) untuk memperbaiki nilai Bahasa Indonesia di sekolah menengah pertama pada ujian nasional. Sampel (N=72) adalah siswa dari sekolah percontohan yang berstandar nasional, yang memiliki nilai rata- rata di bawah KKM untuk Bahasa Indonesia. Sampel dibagi dua: 36 siswa sebagai kelompok eksperimen dan menerima pembelajaran kooperatif STAD, dan 36 siswa lainnya sebagai kelompok kontrol yang memakai pembelajaran tradisional. Studi ini menggunakan desain eksperimen dengan pra- dan pasca-uji dengan replikasi bergantian. Hasil menunjukkan (p< .05) bahwa pembelajaran kooperatif STAD meningkatkan nilai Bahasa Indonesia pada siswa sekolah menengah pertama